Vibrational signatures of the water behaviour upon confinement in nanoporous hydrogels. Issue 17 (15th April 2016) - Rossi, B.; Venuti, V.; Mele, A.; Punta, C.; Melone, L.; D'Amico, F.; Gessini, A.; Crupi, V.; Majolino, D.; Trotta, F.; Masciovecchio, C.
Abstract : Vibrational spectroscopy is used to investigate how the hydrogen-bond dynamics of water is influenced by nano-confinement and hydrophobic/hydrophilic solvation effects. Abstract : The fundamental question of how the reorganization of the hydrogen-bond (HB) network of water is influenced by the combination of nano-confinement and hydrophobic/hydrophilic solvation effects is addressed here using a spectroscopic study of water absorbed in a model, pH-sensitive polysaccharide hydrogel. The effects of temperature, hydration level and pH on the vibrational dynamics associated with the water molecules and the polymer skeleton are disentangled and analysed by a complementary and combined use of UV-Raman scattering and IR spectroscopy. The experimental data give evidence that the solvation effects in the hydrogel matrix are essentially dominated by the hydration of more hydrophobic parts of the polymer network, while the effect of pH on the HB reorganization of confined water molecules is found to be similar to that induced by cooling of the system. A tentative explanation of these results has been provided in terms of interplay between different kinds of interactions, i.e. hydrophobic vs. hydrophilic.